Mycorrhizas from the tropical dry forest and other fungal symbioses - Álvarez-Manjarrez, Julieta; Solís Rodríguez, Abraham Ulises; Villarruel-Ordaz, José Luis; Ortega-Larrocea, María del Pilar; Garibay-Orijel, Roberto (Instituto de Ecología, A.C., 2021)
Background and Aims: The knowledge on plant diversity in the tropical dry forest is constantly increasing, but the knowledge of its mycorrhizal symbioses is scarce. The mycorrhizal status and its morphology provide important information on its ecological role in these ecosystems. The aim of this study was to describe the morphology and fungal association types that some dominant arboreal stratum plants establish in the tropical deciduous forest in both dry and rainy seasons. Methods: Root sampling was performed along the Mexico Pacific coast in Chamela, Jalisco, from 2012 to 2014, and from Puerto Escondido to Salina Cruz, Oaxaca, in 2016. Root samples were collected with soil cores and tracking them from the trunk of Achatocarpus gracilis, Achatocarpus spp., Coccoloba barbadensis, C. liebmannii, Cordia elaeagnoides, Guapira petenensis, Lonchocarpus sp., Ruprechtia fusca, and R. aff. pallida. Each root was reviewed under the stereomicroscope for mycorrhizae; some roots were clarified, stained and mounted on slides; anatomical sections were made, photographs were taken with an optical microscope and the rhizospheric associations were described according to the morphological referents for each type of mycorrhiza. Key results: All plants had active mycorrhizal associations in dry and rainy seasons. Sixty-four ectomycorrhizal morphotypes were described presenting the following morphological variants: zonation of the mantle in secondary roots or incipient mantle formation; absence of branching; absence of Hartig net or presence with intracellular structures. Achatocarpus presented dual mycorrhizae of ectomycorrhizae with arbuscular mycorrhizae. Conclusions: Our results coincide on the ectomycorrhizal morphological differences previously observed in Nyctaginaceae in Ecuador and Brazil, and we extend these observations to more families within Caryophyllales and the family Fabaceae. Our observations, together with previous reports, make us propose a new morphological concept of "incipient" ectomycorrhiza for tropical angiosperms.